Hypogammaglobulinaemia associated with normal or increased IgM (the hyper IgM syndrome): a case series review. Issue 2 (August 1994) - Banatvala, N; Davies, J; Kanariou, M; Strobel, S; Levinsky, R; Morgan, G
Abstract : The clinical and immunological aspects of 16 children with the syndrome of hypogammaglobulinaemia associated with normal or increased IgM (the hyper IgM syndrome) and their responses to treatment are reviewed. Increased concentrations of IgM, neutropenia, and recurrent infections could usually be controlled by antimicrobial and intravenous immunoglobulin treatment. Together with the bacterial infections characteristic of hypogammaglobulinaemia, these patients often developed opportunistic infections, including Pneumocystis carinii pneumonia, often presenting in the first year of life. The occurrence of sclerosing cholangitis, neurological complications, and neutropenia may be a result of an underlying cell mediated immune deficiency, autoimmunity, or infection. Despite a high incidence of opportunistic infections, immunological investigations did not show any abnormality of T cell function. These findings are discussed in the light of the recent demonstration that the lack of expression of a T lymphocyte activation antigen is the molecular basis of the X linked form of the disorder.